CHEMICAL COMPOUNDS OF BEES IN QUR’AN - Zulkarnain Zulkarnain; Suprapto Suprapto (Lantanida Journal, 2022)
Qur’an surah An-Nahl verses 68 and 69 provide information about the nature of bees and their benefits for human life. Allah inspires bees to build nests and find food in trees, mountains, and places made by humans. This study aims to examine scientific information on bees in Surah An-Nahl verses 68 and 69. The research method is library research. The results showed that bees in Surah An-Nahl verses 68 and 69 produce honey, have a good life, have great teamwork, and give benefits to human life. Bee gives people good role models for human society, teamwork, and lifestyle. In science, bees produce pheromone chemical compounds that play a role in communication between bees in the colony. The pheromones produced by the queen bee can regulate the male bees and worker bees to be loyal to the queen bee and carry out their duties well. Qur’an Surah An-Nahl verses 68 and 69 give us information about the bee and honey. Allah gives a message to people to live like a bee to have a good social, good lifestyle, don’t destroy the environment, and give benefits to people like honey. Rasullullah advised us to consume honey for treatment. Honey functions as an antioxidant, anticancer, and energy source, healthy heart, control sugar level, and maintain a healthy body. Bee food is nectar, good nectar will produce high-quality honey. Chemical compounds that are often found in honey like glucose, flavonoid, alkaloid, saponin, and glycoside.